Hydrology controls recruitment of two invasive cyprinids: bigheaded carp reproduction in a navigable large river - Daniel K. Gibson-Reinemer; Levi E. Solomon; Richard M. Pendleton; John H. Chick; Andrew F. Casper (PeerJ, 2017)
In the Mississippi River Basin of North America, invasive bigheaded carp (silver carp Hypophthalmichthys molitrix and bighead carp H. nobilis, also referred to as Asian carp) have spread rapidly over the past several decades. In the Illinois River, an important tributary of the Upper Mississippi River, reproduction appears to be sporadic and frequently unsuccessful, yet bigheaded carp densities in this river are among the highest recorded on the continent. Understanding the causative factors behind erratic recruitment in this commercially-harvested invasive species is important for both limiting their spread and managing their harvest. We analyzed weekly catch records from 15 years of a standardized monitoring program to document the emergence of age-0 bigheaded carp in relation to environmental conditions. The appearance of age-0 fish was generally linked to hydrographic attributes, which probably serve as a cue for spawning. However, we found profound differences in the number of age-0 fish among years, which varied by as much as five orders of magnitude in successive years. The strong link between summer flooding and age-0 fish production we observed emphasizes the importance of understanding the hydrologic context in which sustained invasions occur. Despite evidence of sporadic recruitment, bigheaded carp populations in the Illinois River appear to be consistent or increasing because of particularly strong, episodic year classes.